Impact of Cookware Types on Leaking Heavy Metals into Food based on pH Values, and their Potential Impact on the Health Status of a Saudi Sample using a Survey Study Design - Al-Faki, Waheeba Ahmed; Al-Shabrami, Ruya Mohammed; Aba Al-Khail, Mudhi Abdullah; Al-Muzaini, Hala AbdulAziz; Al-Ghafis, Aroob Ahmed; Al-Adl, Safyah Ahmed; Al-Aqeel, Aljouharah Khaled; Al-Batah, Mashael Ali (Journal of agricultural, environmental and veterinary sciences, 2023)
This study aimed to measure the leaked metal concentrations in cooked food using three types of cookware (stainless steel (18/10), cast iron, and aluminum). Two types of vegetables were used based on their pH values, tomatoes (pH 4.30-4.90) and zucchini (pH 9), as acidic and basic food materials. In addition, a survey study was performed on a randomly chosen Saudi sample to investigate the impact of their income, age, and awareness level in choosing between the different cookware available in the market, as well as to investigate the impact of the used cookware on their health status. The results showed that cooking acidic food (e.g., tomatoes) in aluminum pots can lead to an increase in the concentrations of leaked metals into the food such as leaking copper (0.27mg/kg), iron (3.048mg/kg), aluminum (0.91mg/kg) and magnesium (95.13 mg/kg) but no change in the concentrations of leaked metals into the food such as Chromium and Nickle (
Keywords: cookware; heavy metals; pH; zucchini; tomatoes; aluminum; cast iron; stainless steel